Governance-Driven Stunting Reduction in an Archipelagic Regency: Community-Based Implementation in Bintan, Indonesia - Friska Agustina Sianturi; Darmanto Darmanto; Rudi Subiyakto (Journal Public Policy, 2026)
This study aims to analyze how local governance shapes the implementation of community-based stunting reduction programs in Bintan Regency, Indonesia, an archipelagic and semi-rural area facing administrative and logistical challenges. A qualitative descriptive design was employed through semi-structured interviews with 15 key informants, including village heads, midwives, community health cadres, health officials, and members of the Stunting Reduction Acceleration Team (TPPS). Data were analyzed thematically using five governance dimensions: political commitment, intersectoral coordination, program leadership, data and monitoring systems, and community participation. The findings show that political commitment and community participation were relatively strong, as reflected in village fund allocation, active local leadership, nutrition education, home visits, and community-based initiatives such as foster-home activities. However, inter-sectoral coordination, data utilization, and frontline leadership remained uneven across subdistricts and villages, often depending on informal coordination and individual initiative. The study concludes that stunting reduction in Bintan is not merely a technical health intervention, but a local governance challenge. Strengthening institutional coordination, digital data systems, frontline capacity, and sustained community engagement is essential for improving the effectiveness, equity, and sustainability of stunting reduction programs.